Basic taste characteristics of flavor material from cultured Takifugu obscurus by‐products. (14th January 2020) - Liao, Ya; Wang, Wenli; Chen, Gaole; Zhang, Ninglong; Liu, Yuan
Abstract: Takifugu obscurus ( T. obscurus ) by‐products (fish heads and bones) account for about 35% of total weight. In order to improve its availability, flavor materials based on T. obscurus by‐product have been developed through enzymatic hydrolysis and Maillard thermal reaction. However, their basic taste characteristics have not been extensively investigated. In this study, the taste intensities of T. obscurus flavor materials (protein hydrolysates and Maillard reaction products) at different concentrations, pH, and temperatures were compared and distinguished by sensory evaluation combined with electronic tongue analysis. Results showed that T. obscurus by‐products protein hydrolysates (TBPH) had the optimal taste intensities (mainly umami taste) at 5.0 g/L, pH 6.5, and Maillard reaction products (MRPs) were at 4.0 g/L, pH 7.0. They both possessed excellent thermal stability, and their recognition thresholds were 0.08 g/100 mL for TBPH and 0.03 g/100 mL for MRPs, respectively. This study would lay a theoretical foundation to understand the basic flavor characteristics of T. obscurus by‐products. Abstract : Flavor materials based on Takifugu obscurus ( T. obscurus ) by‐products (fish heads and fish bones) have been developed through enzymatic hydrolysis and Maillard thermal reaction. The taste intensities of two products at different doses, pH, and temperatures were compared and distinguished by sensory evaluation combined with electronic tongue analysis. Takifugu obscurus by‐products protein hydrolysates (TPPH) presented the optimal taste intensities (mainly umami taste) at 5.0 g/L, pH 6.5, and Maillard reaction products (MRPs) were at 4.0 g/L, pH 7.0. They both had excellent thermal stability, and their recognition thresholds were 0.08 g/100 mL and 0.03 g/100 mL, respectively. This study would lay a theoretical foundation to apply the basic flavor characteristics of T. obscurus by‐products into flavor agents.